DNA replication facilitates the action of transcriptional enhancers in transient expression assays. - Wilson, A C (1993)
We demonstrate a general role for DNA replication in the activation of gene transcription in transient transfection assays. The effect is observed for a wide range of genes and cell types, transfected by a number of protocols and is independent of increased template copy number. Replication does not stimulate transcription driven by proximal promoter elements alone but requires a functional enhancer element. This synergy between an active replication origin and an enhancer is not confined to elements from viruses such as SV40, which undergo an early to late switch in gene expression that is tightly coupled to replication, since the enhancer-containing long terminal repeats from retroviruses are strongly stimulated by replication. Furthermore, synthetic enhancers consisting of multimerised binding sites for one or two factors are also subject to replication-activation. The diversity of synthetic and natural enhancers used in this study suggests that replication and transcription do not share a common protein factor. We propose that replication leads to chromatin modifications that facilitate enhancer action.